2014
DOI: 10.1002/hyp.10199
|View full text |Cite
|
Sign up to set email alerts
|

Rapid expansion of glacial lakes caused by climate and glacier retreat in the Central Himalayas

Abstract: Abstract:Glacial lake outburst floods are among the most serious natural hazards in the Himalayas. Such floods are of high scientific and political importance because they exert trans-boundary impacts on bordering countries. The preparation of an updated inventory of glacial lakes and the analysis of their evolution are an important first step in assessment of hazards from glacial lake outbursts. Here, we report the spatiotemporal developments of the glacial lakes in the Poiqu River basin, a trans-boundary bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 57 publications
5
90
0
Order By: Relevance
“…In contrast, Zhang et al (2015) attribute the observed increases in lake surface areas since the 1990s across the entire Pamir-Hindu Kush-Karakoram-Himalayas region and the Tibetan Plateau region to enhanced glacier melting. Wang et al (2015) reached similar conclusions in a basin located in the south-central Himalaya. In our opinion, the divergences in the causes leading to the lake surface area variations in central Asia are due to the fact that different types of glacial lakes (described below) have been considered in these studies.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, Zhang et al (2015) attribute the observed increases in lake surface areas since the 1990s across the entire Pamir-Hindu Kush-Karakoram-Himalayas region and the Tibetan Plateau region to enhanced glacier melting. Wang et al (2015) reached similar conclusions in a basin located in the south-central Himalaya. In our opinion, the divergences in the causes leading to the lake surface area variations in central Asia are due to the fact that different types of glacial lakes (described below) have been considered in these studies.…”
Section: Introductionsupporting
confidence: 67%
“…Fujita et al, 2009;Gardelle et al, 2011). Therefore we did not consider the co-registration error because the comparison was not performed pixel by pixel, at the entity level (pond) (Salerno et al, 2012Thakuri et al, 2016;Wang et al, 2015). The LRE is limited by the resolution of the source data.…”
Section: Uncertainty Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several authors have documented a net increase in supraglacial pond area over recent decades (e.g. Gardelle et al 2011;Nie et al 2013;Wang et al 2015;Watson et al, 2016). These supraglacial ponds can efficiently absorb and transmit thermal energy to adjacent ice cliffs (Sakai et al, 2000;Miles et al, 2016), and promote cliff calving rates of tens of metres per year (Table 1) (Benn et al, 2001).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Wang et al (2015b) found that glacial lakes in the central Himalaya have expanded significantly (122.1%) from 1976 to 2010, and Schwanghart et al (2016) analyzed hydropower installations in the Himalaya and found that about 257 hydropower plants are exposed to GLOF risk. Allen et al (2016) performed a first-order assessment of GLOF risk across the Himalayan state of Himachal Pradesh (HP), Northern India, including locations where future lakes might form.…”
mentioning
confidence: 99%